Pendekatan Solution Focus Brief Counseling (SFBT) Format Kelompok dalam Menangani Masalah Prokrastinasi Akademik Siswa - Syaddiyah, Halimahtun; Karneli, Yeni; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Academic procrastination is a common issue that negatively affects students’ performance and mental well-being, thus requiring an effective intervention approach. This article aims to examine the application of Solution-Focused Brief Therapy (SFBT) as a counseling method to address academic procrastination and other psychosocial problems in school settings. This research adopts a qualitative method using a literature review. Data were collected through documentation and analyzed using content analysis techniques. The findings indicate that SFBT is effective in enhancing students’ self-esteem, self-efficacy, and emotional regulation while significantly reducing academic procrastination. These results support constructivist and positive psychology theories in educational contexts. This study offers practical implications for school counselors in designing solution-focused interventions. Further research is recommended to empirically test SFBT’s effectiveness through field studies.